Efficacy of an online cognitive behavioral therapy program developed for healthcare workers during the COVID-19 pandemic: the REduction of STress (REST) study protocol for a randomized controlled trial - Weiner, Luisa; Berna, Fabrice; Nourry, Nathalie; Severac, François; Vidailhet, Pierre; Mengin, Amaury C. (Current controlled trials in cardiovascular medicine, 2020)
Background The acknowledgment of the mental health toll of the COVID-19 epidemic in healthcare workers has increased considerably as the disease evolved into a pandemic status. Indeed, high prevalence rates of depression, sleep disorders, and post-traumatic stress disorder (PTSD) have been reported in Chinese healthcare workers during the epidemic peak. Symptoms of psychological distress are expected to be long-lasting and have a systemic impact on healthcare systems, warranting the need for evidence-based psychological treatments aiming at relieving immediate stress and preventing the onset of psychological disorders in this population. In the current COVID-19 context, internet-based interventions have the potential to circumvent the pitfalls of face-to-face formats and provide the flexibility required to facilitate accessibility to healthcare workers. Online cognitive behavioral therapy (CBT) in particular has proved to be effective in treating and preventing a number of stress-related disorders in populations other than healthcare workers. The aim of our randomized controlled trial study protocol is to evaluate the efficacy of the ‘My Health too’ CBT program—a program we have developed for healthcare workers facing the pandemic—on immediate perceived stress and on the emergence of psychiatric disorders at 3- and 6-month follow-up compared to an active control group (i.e., bibliotherapy). Methods Powered for superiority testing, this six-site open trial involves the random assignment of 120 healthcare workers with stress levels > 16 on the Perceived Stress Scale (PSS-10) to either the 7-session online CBT program or bibliotherapy. The primary outcome is the decrease of PSS-10 scores at 8 weeks. Secondary outcomes include depression, insomnia, and PTSD symptoms; self-reported resilience and rumination; and credibility and satisfaction. Assessments are scheduled at pretreatment, mid-treatment (at 4 weeks), end of active treatment (at 8 weeks), and at 3-month and 6-month follow-up. Discussion This is the first study assessing the efficacy and the acceptability of a brief online CBT program specifically developed for healthcare workers. Given the potential short- and long-term consequences of the COVID-19 pandemic on healthcare workers’ mental health, but also on healthcare systems, our findings can significantly impact clinical practice and management of the ongoing, and probably long-lasting, health crisis. Trial registration ClinicalTrials.gov NCT04362358 , registered on April 24, 2020.